Skrining fitokimia dan aktivitas antioksidan ekstrak etanol daging buah pala (Myristica fragrans) kawasan Aceh Selatan, Indonesia. - Azhari , Saiful; Kurniaty , Rina; Yusuf, Muhammad; Zulyani , Riza; Mahmudi , Mahmudi; Rani, Wahyu Mustika; Farida , Mutia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
The nutmeg fruit (Myristica fragrans) shows the presence of secondary metabolite compounds and has antioxidant activity. The nutmeg examined in this study is the flesh of the fruit and dried for seven days to obtain simplisia. The extraction process is by maceration method using 96% ethanol solvent. Based on the results of phytochemical screening of ethanol extracts of nutmeg flesh showed the presence of secondary metabolite compounds, which are groups of alkaloids, steroids, saponins and flavonoids. The results of antioxidant activity of ethanol extract of nutmeg flesh have an IC50 value of 22.88 ppm. In this study using vitamin C as a positive control for comparison with the IC50 value obtained is 3.82 ppm. The more secondary metabolite compounds in an extract, the higher the antioxidant activity.